Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Inverse laplace transform question

  1. Nov 22, 2006 #1
    How do i find the inverse laplace transform of s/(s-2)^2
     
  2. jcsd
  3. Nov 22, 2006 #2
    take the transform of [tex] f(t)=(1+t)e^{2t} [/tex]

    using the "shift" property so..

    [tex] F(s+a)=L[e^{-at}f(t)] [/tex] using

    [tex] \frac{s+2}{s^{2}}=s^{-1}+2s^{-2} [/tex]

    the inverse of above is just 1+t then multiply it by exp(2t) and you get it without recalling "residue theorem"...:tongue2:
     
  4. Jul 21, 2007 #3
    Use partial fractions:

    [tex]\frac{s}{(s-2)^2} = \frac{A}{(s-2)^2} + \frac{B}{s-2}[/tex]

    To find A, multiply both sides by [tex]s-2[/tex] and evaluate at [tex]s=2[/tex]:

    [tex]s = A[/tex]

    [tex]A = 2[/tex]

    Now to find B, go back to the original expression again, and multiply (again) both sides by [tex]s-2[/tex],
    then differentiate with respect to s and evaluate at [tex]s=2[/tex]:

    [tex]\frac{d}{ds}s = \frac{d}{ds}[B(s-2)][/tex]

    [tex]B = 1[/tex]

    Now plug A and B into the original expression:

    [tex]\frac{2}{(s-2)^2} + \frac{1}{s-2}[/tex]

    So the inverse Laplace would be:

    [tex]L^{-1} = [2te^{2t}+e^{2t}] u(t)[/tex]
     
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?



Similar Discussions: Inverse laplace transform question
Loading...